Limited role of culture conversion for decision-making in individual patient care and for advancing novel regimens to confirmatory clinical trials. Issue 1 (December 2016) - Phillips, Patrick; Mendel, Carl; Burger, Divan; Crook, Angela; Nunn, Andrew; Dawson, Rodney; Diacon, Andreas; Gillespie, Stephen
Abstract Background Despite recent increased clinical trials activity, no regimen has proved able to replace the standard 6-month regimen for drug-sensitive tuberculosis. Understanding the relationship between microbiological markers measured during treatment and long-term clinical outcomes is critical to evaluate their usefulness for decision-making for both individual patient care and for advancing novel regimens into time-consuming and expensive pivotal phase III trials. Methods Using data from the randomized controlled phase III trial REMoxTB, we evaluated sputum-based markers of speed of clearance of bacilli: time to smear negative status; time to culture negative status on LJ or in MGIT; daily rate of change of log10 (TTP) to day 56; and smear or culture results at weeks 6, 8 or 12; as individual- and trial-level surrogate endpoints for long-term clinical outcome. Results Time to culture negative status on LJ or in MGIT, time to smear negative status and daily rate of change in log10 (TTP) were each independent predictors of clinical outcome, adjusted for treatment (p <0.001). However, discrimination between low and high risk patients, as measured by the c-statistic, was modest and not much higher than the reference model adjusted for BMI, history of smoking, HIV status, cavitation, gender and MGIT TTP. Conclusions Culture conversion during treatment for tuberculosis, however measured, has only a limited role in decision-making for advancing regimens into phase III trials or in predicting the outcome of treatment for individual patients. REMoxTB ClinicalTrials.gov number: NCT00864383.